1998
DOI: 10.1093/bja/81.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1 MAC desflurane on cerebral metabolism, blood flow and carbon dioxide reactivity in humans

Abstract: We investigated the cerebral haemodynamic effects of 1 MAC desflurane anaesthesia in nine male patients scheduled for elective coronary bypass grafting. For the measurement of cerebral blood flow (CBF) a modified Kety-Schmidt saturation technique with argon as inert tracer gas was used. Measurements of CBF were made before induction of anaesthesia and 30 min after induction under normocapnic, hypocapnic and hypercapnic conditions in sequence. Changes in mean arterial pressure after induction of anaesthesia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…Therefore, what is measured clinically is the result of a subtle balance between these two antagonizing effects. It is possible that at the higher desflurane concentration the cerebral vasconstriction as a result of the decreased CMRO 2 becomes more prominent, as suggested by Mielck et al 3 In that study, CCO 2 R was preserved at 1.0 MAC desflurane.…”
Section: Me Et Th Ho Od Ds S After Approval By the Institutional Rementioning
confidence: 56%
See 2 more Smart Citations
“…Therefore, what is measured clinically is the result of a subtle balance between these two antagonizing effects. It is possible that at the higher desflurane concentration the cerebral vasconstriction as a result of the decreased CMRO 2 becomes more prominent, as suggested by Mielck et al 3 In that study, CCO 2 R was preserved at 1.0 MAC desflurane.…”
Section: Me Et Th Ho Od Ds S After Approval By the Institutional Rementioning
confidence: 56%
“…Studies in adults have reported that CCO 2 R is preserved during desflurane anesthesia. [2][3][4] In children, the effects of desflurane on CCO 2 R are not as well defined. In a study of ten children, 4 cerebral blood flow velocity (CBFV) was recorded during the first ten minutes of desflurane administration while the EtCO 2 was changed from 40 to 30 mmHg.…”
Section: Méthode : Les Enfants Choisis Devaient Subir Une Interventiomentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical concentrations, desflurane and isoflurane preserve reactivity of cerebral circulation and coupling of changes in CO 2 and metabolism to blood flow in the brain. 16 In the presence of sevoflurane autoregulation of cerebral blood flow is preserved below 1.5 MAC. 17 …”
Section: Central Nervous System Effectsmentioning
confidence: 99%
“…The cardiovascular effects of desflurane manifest themselves mostly as a dose-dependent increase in heart rate and a reduction in arterial pressure, resulting mainly from dilatation of the vascular bed with the resultant decrease in peripheral resistance, and from negative inotropic action, albeit to a lesser extent [1, [5][6][7][8][9]. As in the peripheral circulation, desflurane dilates the cerebral vessels, which results in increased cerebral blood volume (CBV) likely to lead to increases in intracranial pressure (ICP) [6,10,11]. The factors determining intracranial homeostasis include cerebral blood flow (CBF), cerebral metabolic rate (CMR), autoregulation and reactivity of the cerebral vessels to PaCO 2 .…”
mentioning
confidence: 99%